Response to Howard and Walters. Issue 2 (14th July 2014) - Lust, Ellen
Abstract : This response points to three critical problems in Explaining the Unexpected . First, the authors' contention that scholars ignored "everyday contestation, " including changing citizen-state relations, emerging venues of political participation, and the potential for mobilization, is based on a selective reading of the literature on politics in the Arab world before 2011. Second, their assertion that existing paradigms hindered scholars' ability to understand change mischaracterizes the literature on enduring authoritarianism. Scholars did not argue that regime breakdown was impossible before 2011 but rather sought to understand why authoritarian regimes were sustained. Long before the uprisings, they recognized the factors that could make breakdown possible. Third, Howard and Walters' conclusion that Middle East scholars' fundamental paradigms and their focus on regime type will lead them to treat "utterly remarkable waves of mass mobilization as politically inconsequential" is misplaced. The literature has and continues to explore a wide range of issues that extend far beyond democratization, and recent scholarship has examined varied aspects of the diverse political processes and outcomes witnessed since 2011. Explaining the Unexpected misses the mark on many points, but it does provide a useful platform for scholars to reflect on problems facing comparative politics. These include the blinders resulting from the normative biases underpinning the discipline and the need for a nuanced discussion about how, and to what extent, scholars facing rapid, regional transformations can learn from the study of similar experiences in other regions.